Bioinspired Smart Nanosystems in Advanced Therapeutic Applications - Singh, Satya P.; Sirbaiya, Anup Kumar; Mishra, Anuradha (Pharmaceutical Nanotechnology, 2019)
Background: Nanoparticle technologies used for human administration must be designed to interact with a living host environment. The idea about bioinspired smart drug delivery carriers includes the development of biocompatible nanomaterials which can be further loaded with the drug for specific targeted drug delivery applications. Objective: Biosmart nanosystems are used for several applications in the delivery of drugs and pharmaceuticals for their therapeutic applications like biological markers, diagnostic purposes such as imaging applications and also for gene therapy. Thus, the bioinspired nanocarriers are capable of carrying biologically active molecules to the target sites. This bioinspired nanosystem constitutes of lipids, polymers and biomaterials which utilizes various responsive sensors for targeted drug delivery systems. However, external conditions such as heat, light, magnetic or electric field and ultrasounds, along with temperature, altered pH and ionic strength can affect the bioinspired smart nanosystem for drug delivery. Conclusion: The present review focuses on challenges for the development of bioinspired smart nanocarriers for the management of various disorders.
Keywords: Biosmart drug delivery systems